ImplementationStrategies on Performance Improvement (At PT. Perkebunan NusantaraXII(Persero)) - Ferdy Faizal Prasetya Putra; Bambang Hariadi (Jurnal Ilmiah Mahasiswa FEB, 2012)
Strategyis one determinant ofthe success ofa company, in whichthe strategy isusedforproperdecision makingfor the company tooperateoptimally.Therefor, each companymusthave a strategyin order tocontinue to grow. This studyaimed to determine whetherthe strategycurrently usedis usedby the PT.Perkebunan NusantaraXII(Limited)isappropriatein order to increaseperformanceof coffeeproduction, thenwhatexactlystrategiesusedby the company. This research methodusingdescriptive qualitativecase study approach.DataCollection Methodsused twofirstfieldworkthatway; Archive,observations, andinterviews, the secondresearchliterature. From the results ofthe SWOT analysisis knownthat thecondition of the companyis in good shapebecause the powercompany canmaximize thepower toget the opportunity, andthe companycan minimizeweaknessesand overcomethreats coming. In order touse acorporatestrategyGrowthstrategiestobusiness strategieswhileusing the strategyOverallcostLeadership. The results ofthe matrixanalysisof GeneralElectricarabica coffeeisa commoditystrategyandInvestforGrowthandRobustacoffeecommodityisSelectivegrowth.At theArabica coffeecommoditycompanies shouldinvest morebecausethe marketis sobig, especially commodityexportmarket. Addinginvestment incommoditiesarabica coffeein several ways, namely the addition ofland, seed multiplicationandsuperiorplants, and increasedplant maintenance. Forrobustacoffeecommoditycompanies shouldchoosea particularfocus onthe qualitysothe bestqualitylandandaddedthatpoorqualityis reduced, andfurther developedin thelocal market.   Keywords: Strategic Management, Coffee Production,Internaland ExternalFactors, Strategy Implementation